BETA BLOCKER DOSAGE AND USE OVER TIME IN THE SYSTOLIC HEART FAILURE TREATMENT WITH THE IF INHIBITOR IVABRADINE TRIAL (SHIFT) STUDY - Borer, Jeffrey S.; Swedberg, Karl; Komajda, Michel; Ford, Ian; Tavazzi, Luigi; Boehm, Michael; Dominjon, Fabienne; Maya, Juan; Wu, Yuna (Journal of the American College of Cardiology, 2015)
Background: In the SHIFT study, ivabradine, a novel selective inhibitor of the cardiac pacemaker f-current (If) that lowers heart rate, showed significant reduction in cardiovascular mortality or hospitalizations for worsening heart failure vs placebo in patients with chronic systolic heart failure, when added to standard therapy, including beta blockers (BB).